2023
DOI: 10.1002/advs.202206756
|View full text |Cite
|
Sign up to set email alerts
|

An Ionic Liquid Ablation Agent for Local Ablation and Immune Activation in Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma rapidly acquires resistance to chemotherapy, remaining a fatal disease. Immunotherapy is one of the breakthroughs in cancer treatment, which includes immune checkpoint inhibitors, chimeric antigen receptor T‐cell immunotherapy, and neoantigen vaccines. However, immunotherapy has not achieved satisfactory results in the treatment of pancreatic cancer. Immunogenic death comprises proinflammatory cell death, which provides a way to enhance tumor immunogenicity and promote an immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…[23] CA is performed with imaging guidance, allowing precise tumor targeting, and minimizing harm to healthy breast tissue. In the management of bone tumors, CA is a local ablative therapy to alleviate pain, control tumor growth, and preserve limb Combination of CA and thermo-responsive hydrogel containing TLR7 agonist [ 44] Nanoparticle co-loaded with camptothecin and PD-L1 siRNA to improve efficacy [ 45] Radiofrequency Enhancing transformation of electromagnetic waves into phonon vibrations by using DLM-loaded HIONs [ 68] Combining RFA with neoadjuvant oncolytic virus therapy or PD-L1 inhibitor [ 70] Combining lipoxidase/ hemin-loaded PLGA, check point inhibitor, and RFA for tumor regression [ 71] Microwave ablation (MWA) Antennas with smaller diameters minimize off-target damage and improve small lesion ablation [ 117a,118] EF and DOX co-loaded liposomes to reduce incomplete MWA-induced tumor recurrence [ 119] High-intensity focused ultrasound ablation with HIFU [ 166] HIFU-responsive DOX/PFOB-loaded lipid nanoparticles for GBM [ 168] Irreversible electroporation (IRE) Combining IRE with PD1 inhibitor and TLR7 agonist [ 200] Combining IRE with allogeneic NK cell therapy in late-stage pancreatic cancer [ 201] (Continued) Stimuli-responsive water-soluble PSs for cancer treatment [ 237] Combining PDT and HIF-1 inhibitors to overcome hypoxic tumors [ 213a] PSs comprised of non-covalent bonds to achieve controllable photoreactivity and rapid clearance [ 242] Chemical ablation (CA) Choline-based IL that readily diffuses and creates large ablation zones in tumor matrices [ 257] Activate anti-tumor immunity in "cold" tumors by reshaping TME [ 261] Radioablation (RA) Delivers precise doses of radiation to the targeted area to achieve ablation Radiation damages the DNA within the tissues, disrupting their ability to divide and proliferate Combining ICB, chemodynamic therapy, and RA for enhanced antitumor immunity [ 280] function. Studies have shown that patients with metastatic bone lesions experience considerable pain reduction and increased quality of life.…”
Section: Clinical Applications Of Camentioning
confidence: 99%
See 1 more Smart Citation
“…[23] CA is performed with imaging guidance, allowing precise tumor targeting, and minimizing harm to healthy breast tissue. In the management of bone tumors, CA is a local ablative therapy to alleviate pain, control tumor growth, and preserve limb Combination of CA and thermo-responsive hydrogel containing TLR7 agonist [ 44] Nanoparticle co-loaded with camptothecin and PD-L1 siRNA to improve efficacy [ 45] Radiofrequency Enhancing transformation of electromagnetic waves into phonon vibrations by using DLM-loaded HIONs [ 68] Combining RFA with neoadjuvant oncolytic virus therapy or PD-L1 inhibitor [ 70] Combining lipoxidase/ hemin-loaded PLGA, check point inhibitor, and RFA for tumor regression [ 71] Microwave ablation (MWA) Antennas with smaller diameters minimize off-target damage and improve small lesion ablation [ 117a,118] EF and DOX co-loaded liposomes to reduce incomplete MWA-induced tumor recurrence [ 119] High-intensity focused ultrasound ablation with HIFU [ 166] HIFU-responsive DOX/PFOB-loaded lipid nanoparticles for GBM [ 168] Irreversible electroporation (IRE) Combining IRE with PD1 inhibitor and TLR7 agonist [ 200] Combining IRE with allogeneic NK cell therapy in late-stage pancreatic cancer [ 201] (Continued) Stimuli-responsive water-soluble PSs for cancer treatment [ 237] Combining PDT and HIF-1 inhibitors to overcome hypoxic tumors [ 213a] PSs comprised of non-covalent bonds to achieve controllable photoreactivity and rapid clearance [ 242] Chemical ablation (CA) Choline-based IL that readily diffuses and creates large ablation zones in tumor matrices [ 257] Activate anti-tumor immunity in "cold" tumors by reshaping TME [ 261] Radioablation (RA) Delivers precise doses of radiation to the targeted area to achieve ablation Radiation damages the DNA within the tissues, disrupting their ability to divide and proliferate Combining ICB, chemodynamic therapy, and RA for enhanced antitumor immunity [ 280] function. Studies have shown that patients with metastatic bone lesions experience considerable pain reduction and increased quality of life.…”
Section: Clinical Applications Of Camentioning
confidence: 99%
“…[257] IL may reshape the TME by amplifying the maturation of antigen-presenting cells, polarizing macrophages, increasing lymphocyte infiltration, and triggering an immune response against immune-suppressive solid tumors (known as "cold" tumors). [261] This suggests that chemical ablation using IL can activate anti-tumor immune responses and can also be combined with immunotherapy. Similarly, in rat models, sodium hydroxide (NaOH) administered with a concentration of 0.002 mmol L −1 NaOH at 0.05 mL showed a similar effect to the same volume of absolute ethanol or 50% acetic acid, but with less toxicity.…”
Section: Ongoing Research In Chemical Ablationmentioning
confidence: 99%
“…269 Pancreatic ductal adenocarcinoma cells treated with CAGE enhanced immunogenicity and permeability of tumor cells. 270 Mitragotri's team developed a new IL adjuvant synthesized using choline and lactic acid. It had good biocompatibility and a dispersion effect on ovalbumin antigen, induced effective antigen-presenting cell infiltration at the injection site, and generated a strong immune response to antigen.…”
Section: Application Of Ils In Delivery Systemsmentioning
confidence: 99%
“…The diversity of cancer treatment options using ILs is a testament to the ongoing efforts of researchers to find new and innovative ways to treat cancer. The particular physicochemical properties of ILs make them an attractive option for cancer Local ablation and immune activation in pancreatic cancer [82] treatment, offering new possibilities for improving efficacy and reducing the side effects of cancer treatments. As well as acting as therapeutic agents, ILs can combine different therapeutic modalities to achieve synergistic effects in cancer treatment.…”
Section: Ils In Cancer Treatmentmentioning
confidence: 99%